The CHIP-clinic as the catalyst of preventive medicine - Hasselbalch, Hans Carl; Skov, Vibe; Kjaer, Lasse; Knudsen, Trine Alma; Eickhardt-Dalbøge, Christina Schjellerup; Ellervik, Christina; Cordua, Sabrina; Sørensen, Anders Lindholm; Christensen, Sarah Friis; Kristiansen, Marie Hvelplund; Lindholt, Jes Sanddal; Thomassen, Mads; et al. (Frontiers in Hematology, 2024)
Clonal Hematopoiesis of Indeterminate Potential (CHIP) is associated with an increased risk of cardiovascular diseases (CVD) and is a precursor stage to the BCR-ABL negative chronic myeloproliferative neoplasms (MPNs). These diseases are acquired stem cell neoplasms, arising due to mutations in the hematopoietic stem cell. The most prevalent is the JAK2V617F (JAK2) mutation, which potently generates reactive oxygen species (ROS), and accordingly contributes greatly to the chronic inflammatory state and the increased risk of thrombosis in MPNs. The MPNs are largely underdiagnosed blood cancers with a long pre-diagnostic phase of several years, when the elevated blood cell counts are considered reactive to smoking, blood clots, infections or chronic inflammatory diseases. Since the JAK2 mutation as CHIP-JAK2 associates with an increased risk of CVD and an increased risk of hematological and non-hematological cancers there is an urgent need to explore and validate the JAK2 mutation as a novel risk factor for CVD and to establish CHIP-clinics, which in an interdisciplinary collaboration between experts from several disciplines, and ensure timely diagnosis of the undiagnosed MPN patient and associated comorbidities. We envisage studies of the JAK2 mutation in large CVD cohorts to deliver the “Proof of Concept” for the JAK2 mutation to be implemented as a novel, highly important risk factor for CVD. These novel preventive strategies are considered to have the potential of reducing morbidity and mortality in a large population of citizens and patients, carrying the thrombosis- and CVD-promoting JAK2 mutation.